2014
DOI: 10.1021/jz500238z
|View full text |Cite
|
Sign up to set email alerts
|

Submonolayer-Pt-Coated Ultrathin Au Nanowires and Their Self-Organized Nanoporous Film: SERS and Catalysis Active Substrates for Operando SERS Monitoring of Catalytic Reactions

Abstract: For their unique properties, core-shell bimetal nanostructures are currently of immense interest. However, their synthesis is not a trivial work, and most works have been conducted on nanoparticles. We report herein a new synthetic tactic for submonolyer-Pt coated ultrathin Au nanowires (NWs). Besides providing a strong electromagnetic field for Raman signal enhancing, the underlined Au NWs markedly enhanced the catalytic activity of Pt atoms through increasing their dispersity and altering their electronic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…To achieve in situ SERS monitoring, catalytically responsive and SERS active functionalities must be combined into a single platform, which has been realized by assembling SERS active substrates and small metal catalysts [5][6][7][8][9], or coating the SERS active inner core with a catalytic shell [10][11][12][13][14]. Among them, gold-based SERS/catalyst bifunctional systems have been of tremendous interest because gold nanostructures exhibit high SERS activities and superior catalytic properties under mild conditions, which closely depend on their sizes and shapes [15].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve in situ SERS monitoring, catalytically responsive and SERS active functionalities must be combined into a single platform, which has been realized by assembling SERS active substrates and small metal catalysts [5][6][7][8][9], or coating the SERS active inner core with a catalytic shell [10][11][12][13][14]. Among them, gold-based SERS/catalyst bifunctional systems have been of tremendous interest because gold nanostructures exhibit high SERS activities and superior catalytic properties under mild conditions, which closely depend on their sizes and shapes [15].…”
Section: Introductionmentioning
confidence: 99%
“…We further extended this method to fabrication of Ag NPF that had an even better SERS performance and allowed detection of high toxicity aflatoxins down to 10 À8 M. Moreover, the bottom-up approach used in (Au/ Ag) NPF fabrication allowed the doping and even distribution of other functional materials into the nanopores, thus conferring them with SERS activity (Fig. 4A) [27,79,80]. The combination of the SERS activity and the functions of the doped materials endows these hybrid SERS substrates with specific functions, which we termed task-specific SERS substrates.…”
Section: Halide Ion-induced Gelation Of Metal Nanowiresmentioning
confidence: 99%
“…The combination of the SERS activity and the functions of the doped materials endows these hybrid SERS substrates with specific functions, which we termed task-specific SERS substrates. As a proof-of-concept, we coprecipitated nanosorbent (g-Fe 2 O 3 nanosheets, a good sorbent for inorganic Arsenic ions) and nanocatalyst (Pd overlayer/branches) into Ag NPFs, and successfully performed ultra-sensitive SERS detection of arsenic ions in the presence of a high concentration of coexisting ions and monitored the catalyzed reactions with SERS with a millisecond time resolution [27,33].…”
Section: Halide Ion-induced Gelation Of Metal Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decades, many efforts have been made to break the limitation of substrate specificity and to expand SERS applications to other metals, especially the transition metals Pd and Pt, which are widely used in catalysis [15,21,22]. Recently, it was reported that bimetallic/multiple metallic nanomaterials display novel properties distinct from the pure Pd or Pt element nanostructures [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%